2006
DOI: 10.1016/j.molcel.2006.07.007
|View full text |Cite
|
Sign up to set email alerts
|

PCNA Controls Establishment of Sister Chromatid Cohesion during S Phase

Abstract: Accurate segregation of the genetic material during cell division requires that sister chromatids are kept together by cohesion proteins until anaphase, when the chromatids become separated and distributed to the two daughter cells. Studies in yeast revealed that chromatid cohesion is essential for viability and is triggered by the conserved protein Eco1 (Ctf7). Cohesion must be established already in S phase in order to tie up sister chromatids instantly after replication, but how this crucial timing is achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
309
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(338 citation statements)
references
References 39 publications
14
309
1
3
Order By: Relevance
“…Circumstantial evidence has indeed indicated a relationship between DNA replication and the establishment of sister chromatid cohesion. Sister chromatid cohesion requires not only chromosome-bound cohesin complexes but also Eco1 and PCNA, 4,6,28 as well as several accessory factors such as Ctf18. 29,30 These proteins locali�e to replication forks, at least when cells are arrested in early S phase by hydroxy urea (HU) treatment.…”
Section: Ino80 Complex In Sister Chromatid Cohesion Chromosome XV Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Circumstantial evidence has indeed indicated a relationship between DNA replication and the establishment of sister chromatid cohesion. Sister chromatid cohesion requires not only chromosome-bound cohesin complexes but also Eco1 and PCNA, 4,6,28 as well as several accessory factors such as Ctf18. 29,30 These proteins locali�e to replication forks, at least when cells are arrested in early S phase by hydroxy urea (HU) treatment.…”
Section: Ino80 Complex In Sister Chromatid Cohesion Chromosome XV Andmentioning
confidence: 99%
“…Here we have shown that the INO80 chromatin remodeling complex locali�es to replication forks, at least during replication arrest in early S phase cells, and colocali�es with Ctf18 and PCNA, which are involved in cohesion establishment. 6,7 Furthermore, arp8 cells are defective in sister chromatid cohesion and perturbed in the recruitment of Ctf18 and PCNA to replication forks.…”
Section: Ino80 Complex In Sister Chromatid Cohesion Chromosome XV Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoubiquitinated PCNA can be polyubiquitinated by the Rad5-Ubc13-Mms2 complex (Hofmann and Pickart, 1999) to allow error-free mechanisms (Torres-Ramos et al, 2002). Alternatively, K164 of PCNA can be SUMOylated to regulate recombination at the fork (Pfander et al, 2005;Moldovan et al, 2006) via a direct interaction with Srs2 (Pfander et al, 2005), a 3 -5 DNA helicase (Rong and Klein, 1993), thought to exert a negative control on HR (Krejci et al, 2003;Veaute et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, variations in cytosine methylation may be the indirect result of disturbed recruitment of proteins to the replication fork. In yeast, ECO1 can interact with the PCNA subunit 22 , a key regulator of replication fork function, but several other proteins can also interact with PCNA and include ARABI-DOPSIS TRITHORAX-RELATED PROTEIN 5 (ATXR5) and ATXR6. 23 The respective ATXR5/6 loci cause a wide range of defects when mutated, such as re-replication of pericentromeric regions 23 , a phenotype possibly observed in CTF7 mutants.…”
Section: Hypothetical Mechanisms For Ctf7/ Eco1 Functionmentioning
confidence: 99%